The Biographical method and experimental science learning. A theoretical perspective viable in the social sciences (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
In education there is a particular interest in learning because it is part of education and is directly linked to the work of teachers. The objective of this research was to study the use of biographical method as a way to approach the learning of experimental sciences at university level. Qualitative methodology was adapted to the reality that is studied and how to approach it is with the biographical method. We used life stories, in-depth interviews and content analysis to discover the context surrounding the students. This is a unique case study, in a predominantly descriptive to build an interpretation of the actions of the protagonist. The results indicate that learning involves the conscious construction of the individual, which the informant indicated as fundamental the need for synthesis through summary writing, to strengthen and to understand what is learned through a search comprehensive aspects of learning. The results show that the biographical method is a theoretical option recommended approach to learning.
Keywords: education; learning; biographical method; life stories